Induction Chemotherapy Has No Prognostic Value in Patients with Locoregionally Advanced Nasopharyngeal Carcinoma and Chronic Hepatitis B Infection in the IMRT Era - Zhang, Lu-Lu (Transl Oncol, 2017)
BACKGROUND: The effectiveness of induction chemotherapy (IC) followed by concurrent chemoradiotherapy (CCRT) over CCRT alone in patients with locoregionally advanced nasopharyngeal carcinoma (NPC) and chronic hepatitis B infection in the intensity-modulated radiotherapy (IMRT) era is unknown. PATIENTS AND METHODS: A total of 249 patients with stage T1-2 N2-3 or T3-4 N1-3 NPC and chronic hepatitis B infection treated with IMRT were retrospectively reviewed. Propensity score matching (PSM) was employed to balance covariates; 140 patients were propensity-matched (1:1 basis). Survival outcomes in the IC + CCRT and CCRT groups were compared using the Kaplan–Meier method, log-rank test and Cox proportional hazards model. RESULTS: No significant survival differences were observed between IC + CCRT and CCRT (5-year overall survival, 88.3% vs. 82.2%; P = .484; disease-free survival, 73.9% vs. 75.2%; P = .643; distant metastasis-free survival, 84.1% vs. 85.1%; P = .781; and locoregional failure-free survival, 87.9% vs. 85.1%; P = .834). After adjusting for known prognostic factors in multivariate analysis, IC was not an independent prognostic factor for any outcome (all P > .05); subgroup analysis based on T category (T1-2/T3-4), N category (N0-1/N2-3), and overall stage (III/IV) confirmed these results. The incidence of hepatic function damage in the IC + CCRT and CCRT groups was not significantly different. CONCLUSION: IC + CCRT leads to comparable survival outcomes and hepatic function damage compared to CCRT alone in patients with locoregionally advanced NPC with chronic hepatitis B infection in the IMRT era. Further investigations are warranted.